Learning Mathematics Using the Google Meet Application: an Effort to Improve Student Learning Outcomes - Deysti Trifena Tarusu; Rini Angraini; Imriani Moroki; Gita Fajrin Jafar; Lowryk Ochdrico Lahunduitan (Departement of Mathematics Education, 2024)
This research was conducted to improve student learning outcomes in flat-sided building materials taught using the Google Meet application. Classroom Action Research (PTK) was born on class VIII A students of SMP Negeri 2 Tomohon on flat-sided building material. The subjects in this research were 25 students in class VIII A. The implementation of the Google Meet application in PTK activities is carried out in 2 cycles, where each cycle consists of 2 meetings and 1 test, with one meeting lasting 2 x 40 minutes. The results of research in cycle I using the Google Meet application obtained a percentage of student completion of 48%. In cycle II, using the Google Meet application, student completion was 76%. These results show that the Google Meet application can improve learning outcomes.